Exposure and Health Impact Assessment of Essential and Non-essential Elements in Rice Sold on Ghanaian Markets - Jonathan Awewomom; Theresa Yvonne Arhin; Yaw Doudu Takyi; Agyei Gyasi Yaw; Janet Saaka; Francis Opoku; Marina Aferiba Tandoh; Emmanuel Adu Amankwah; Osei Akoto (Environmental Health Insights)
This present study investigated the presence, levels and health impact of some trace elements in rice sold on some Ghanaian markets using an Inductively coupled plasma mass spectrometry (ICP-MS). Analysis with the ICP-MS revealed that, the concentration of essential and non-essential metals followed the order: S > K > P > Mg > Ca > Si > Na > Zn > Mn > Al > Fe > Bi > Cu > Sn > B > Mo > As > Ba > Sb > Ni > Sr > Co > V > Ti > Be > Pb > Cd > Li > Zr > Ag > Y respectively. The results showed that rice for sale on Ghanaian markets are rich sources of S, K, Mg and Ca with moderate levels of essential minerals like Fe, Mn, Zn and Cu. The health impact assessment revealed all samples for population categories recorded hazard quotients greater than 1 for As and P. This implies that As and P could accumulate and adversely affect the health of Ghanaian children, adolescents, adults and the aged. The likely cancer risk (LCR) estimated from this study revealed that in children, adolescents, adults and the aged, As, Pb, Ni and Cd could individually and in combined accumulated concentrations induce carcinogenicity to consumers in Ghana overtime, since their LCR and Total Likely Cancer Risk (TLCR) exceeded the maximum safe limit of 1 × 10 −4 . A bioavailability study is recommended to determine the exact levels of these toxic substances in the body system of consumers to help formulate policies to protect the health of rice consumers in Ghana. Future studies could incorporate a broader dietary exposure assessment and investigate potential mitigating factors, such as rice preparation methods, that could reduce toxic metal concentrations.